I got the answer as $\lambda^2e^{-\lambda t}s(t-s)$ using the properties like independent increment and stationary increments. But I can't seem to understand the steps in the solution of the book.

For reference, the definition followed in the book is, let $\eta_1,\eta_2,\ldots$ be a sequence of independent random variables,each having the same exponential distribution of rate $\lambda$.We put


$N(t)$, where $t\geq0$, is a Poisson process if $N(t)=max\{n:t\geq\xi_n\}$

Solution: Using the fact that $\eta_1,\eta_2,\ldots$ are independent and exponentially distributed, we obtain

$\begin{array} {lcl} P\{N(s)=1,N(t)=2\} & = & P\{\xi_1\leq s<\xi_2\leq t<\xi_3\} \\ & = & P\{\eta_1\leq s<\eta_1+\eta_2\leq t<\eta_1+\eta_2+\eta_3\}\\ &=& \displaystyle\int_{0}^{s}P\{s<u+\eta_2\leq t<u+\eta_2+\eta_3\}\lambda e^{-\lambda u}du\\ &=& \displaystyle\int_{0}^{s}\left(\displaystyle\int_{s-u}^{t-u}P\{t<u+v+\eta_3\}\lambda e^{-\lambda v}dv \right)\lambda e^{-\lambda u}du\\ &=& \displaystyle\int_{0}^{s}\left(\displaystyle\int_{s-u}^{t-u}e^{-\lambda (t-u-v)}\lambda e^{-\lambda v}dv \right)\lambda e^{-\lambda u}du\\ &=& \lambda^2e^{-\lambda t}s(t-s)\end{array}$

I understood the first two lines.For the next step, I thought maybe they used the PDF of the exponential distribution of $\eta_1$ and took the PDF as function of $u$. So the replacing of $\eta_1$ by $u$. But can we just do that? Didn't it become a probability of an event by the second line? So how can we consider a single inequality in it?

I'm trying to self learn Stochastic Process.So my knowledge isn't the best in this. Any help would be appreciated.

Btw I solved the problem just like https://math.stackexchange.com/questions/4356860/let-nt-be-a-poisson-process-calculate-pns-neq-nt-and-pns-0-nt


1 Answer 1


It involves the knowledge of multiple integrals.

Define $D=\{(\eta_1,\eta_2,\eta_3): \eta_1\leq s<\eta_1+\eta_2<t<\eta_1+\eta_2+\eta_3\}$,

and $A(u)=\{(\eta_2,\eta_3): s<u+\eta_2<t<u+\eta_2+\eta_3\}$, where $u \leq s$.

Given that $\eta_1,\eta_2,...$ are mutually independent, the PDF $f(\eta_1,\eta_2,\eta_3)=P(\eta_1)P(\eta_2)P(\eta_3)$.

We have

$$\begin{aligned}P(\eta_1<s<\eta_1+\eta_2<t<\eta_1+\eta_2+\eta_3)&=\iiint_Df(\eta_1,\eta_2,\eta_3) d\eta_1d\eta_2d\eta_3\\ &=\iiint_DP(\eta_1)P(\eta_2)P(\eta_3) d\eta_1d\eta_2d\eta_3\\ &=\iiint_DP(u)P(\eta_2)P(\eta_3) dud\eta_2d\eta_3\\ &=\int_0^sP(u)(\iint_{A(u)}P(\eta_2)P(\eta_3)d\eta_2d\eta_3)du\\ &=\int_0^s\lambda e^{-\lambda u}(\iint_{A(u)}P(\eta_2)P(\eta_3)d\eta_2d\eta_3)du\\ &=\int_0^s\lambda e^{-\lambda u}P(s<u+\eta_2\leq t<u+\eta_2+\eta_3) du \end{aligned}$$

Above describes the deduction process from the second line to the third line. The same reasoning applies to deducing the result from the third line.

  • $\begingroup$ It kind of makes sense.Guess I need to revise some concepts for this $\endgroup$
    – A Y
    Jun 19, 2023 at 17:05

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.